2022
DOI: 10.32854/agrop.v15i9.2261
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of herbal choline in productive performance and blood metabolites of ewes

Abstract: Objective: To evaluate the effect of different levels of protected herbal choline (CHP) on productive performance, carcass characteristics, and serum metabolites in ewes. Design/Methodology/Approach: Fifty-two Hampshire × Suffolk ewes (29.95 ± 3.90 kg of initial live weight, PV) were randomly assigned to one within four treatments: 0, 0.3, 0.6 and 0.9% choline kg-1 dry matter (MS). The experimental design was complete randomized, in order to detect linear or quadratic trends. Results: No treatment effects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Microarrays allow for a better understanding of the genome and transcriptome, as shown by evaluating all genes in the phenomenon studied [ 78 ]. The overall results in pathways allow us to explain the improvements in performance parameters in sheep [ 28 , 35 , 37 , 43 , 44 ], antioxidant status [ 36 ], and immune response and cattle health [ 41 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Microarrays allow for a better understanding of the genome and transcriptome, as shown by evaluating all genes in the phenomenon studied [ 78 ]. The overall results in pathways allow us to explain the improvements in performance parameters in sheep [ 28 , 35 , 37 , 43 , 44 ], antioxidant status [ 36 ], and immune response and cattle health [ 41 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ruminant blood tests have been reported in 12 experiments [ 28 , 35 , 36 , 37 , 38 , 41 , 42 , 43 , 44 , 45 , 48 , 49 ]; unfortunately, the blood concentration of Ptdcho was evaluated (evidence of exceeding the metabolites of Ptdcho) only in one experiment [ 28 ], whereby increasing the dose of BioCholine caused a linear increase in blood Ptdcho. The other metabolites shown are indicators of effects in the animal due to the polyherbal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, many investigators focused on antibiotics substitutes, namely feed additives or supplements as probiotics (as single or mixed strains) to the animal feed [ 5 , 6 ]. Probiotics have been shown to have positive effects on the microbial ecosystem [ 7 ], nutrient synthesis [ 4 , 8 ], growth performance [ 9 ], carcass weight [ 10 , 11 ], muscle production and meat quality [ 3 , 12 , 13 , 14 ], prevention of enteric diseases [ 15 ], and immunity [ 16 ]. A study showed that 2.5 months of dietary supplement of probiotics ( Lacticasebacillus rhamnosus ; Saccharomyces cerevisiae ) could maintain microbial balance in the gastrointestinal tracts of weanling lambs [ 6 ].…”
Section: Introductionmentioning
confidence: 99%